Consistency and inconsistency in learning experiences across the early grades - Christopher, Caroline; Nesbitt, Kimberly (Frontiers in Education, 2023)
The personal and societal benefits of providing quality early education experiences are well supported by research. While there is growing evidence as to the specific features and experiences that define quality and effective early education classrooms, there remain open questions as to whether these features and experiences differ as a function of grade level. The current study aims to examine how key features of prekindergarten through 2nd grade U.S. classrooms vary (or remain consistent) across grade levels. Using a behavioral-based observation system, this study found that across the early school years, instruction tends to focus on basic skills provided in whole-class groupings that were related to passive participation from students. Across all grades, there was a predominant focus on language arts. These findings highlight the need to consider the appropriateness of pushing down the academic demands typical in 1st grade into prekindergarten and kindergarten classrooms in the U.S.